IMPLIKASI SOSIAL EKONOMI KEBERADAAN MAHASISWA PENDATANG TERHADAP MASYARAKAT SEKITAR KAMPUS UNIVERSITAS TEUKU UMAR - Arhamar Ridha; Nirzalin Nirzalin; Mursyidin Mursyidin (Lembaga Studi Agama dan Masyarakat Aceh (LSAMA), 2023)
This thesis examines the Socio-Economic Implications of the Existence of Migrant Students in Communities Around the Teuku Umar University Campus. The existence of Immigrant Students at Teuku Umar University certainly provides many changes to the socio-economic community. A very visible aspect is the change in the socio-economic conditions of residents around the campus. Immigrant students have a positive impact in improving the socio-economic life of the surrounding community. The purpose of this study was to determine the socio-economic implications of the presence of immigrant students in the community around the Teuku Umar University campus and find out what factors influence social change in the community around the Teuku Umar University campus. The population of this research is the community around Teuku Umar University. The sampling technique used is proportional random sampling. The sample in this study were 13 people spread across three villages around the campus. The results of this study indicate that until now the influence of foreign students around Teuku Umar University has not been very significant, but with the presence of newcomer students at Teuku Umar University many positive changes have been produced, for example increasing living standards, increasing income, and changing livelihoods.